Evaluation of the behaviour of unripe banana flour with non-conventional flours in the production of gluten-free bread - Martínez-Castaño, Marcela (Food science and technology international = Ciencia y tecnologia de los alimentos internacional, 2020)
Gluten-free breads were developed by incorporating unripe banana flour in a blend of alternative flour/cassava starch, 45/50. A factorial design was applied to determine the simultaneous effect of percentage of unripe banana flour (2, 8, 15%) and the type of alternative flour (quinoa, oyster mushroom, yellow pea and lentil flour) on structural and colour properties of bread. Principal component analysis was used to evaluate the behaviour of the formulations from a comprehensive perspective. Three formulations, denoted as P8 (pea + 8% unripe banana flour), Q15 (quinoa + 15% unripe banana flour) and L15 (lentil + 15% unripe banana flour) exhibited the closest profiles to reference (wheat bread). Breads with oyster mushroom flour showed a profile significantly different from the rest of formulations. The interactions among the factors were significant for all studied properties and showed that the unripe banana flour fortification did not lead to proportional responses on the bread properties, but the behaviour of unripe banana flour in breadmaking relied on the percentage and the type of alternative flour used. The P8, Q15 and L15 exhibited high fibre content and carbohydrate content lower than the reference. In addition, P8 formulation can be classified as intermediate glycaemic index